1995
DOI: 10.1677/joe.0.1460359
|View full text |Cite
|
Sign up to set email alerts
|

Influence of treatment with the anti-oestrogen 3-hydroxytamoxifen (droloxifene) on plasma sex hormone levels in postmenopausal patients with breast cancer

Abstract: Plasma levels of oestradiol (Oe2), oestrone (Oe1) oestrone sulphate (Oe1S), androstenedione, testosterone, dehydroepiandrosterone (DHEA), dehydroepiandrosterone sulphate (DHEAS), sex hormone-binding globulin (SHBG) and the gonadotrophins (FSH and LH) were determined in 20 postmenopausal women with breast cancer treated with the anti-oestrogen droloxifene (3-hydroxytamoxifen). Plasma oestrogens were measured before and after 3, 6 and 12 months of therapy. The other hormones were measured before and after 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Droloxifene, a structural analogue of tamoxifen (3‐hydroxytamoxifen), behaves as an estrogen agonist in terms of its relation to bone as well as its impact on certain components of the lipid and coagulation profiles 12. Its potential for use in advanced breast cancer was suggested by its ability to modulate plasma sex hormone levels in a direction resembling that seen during tamoxifen treatment in postmenopausal women with breast cancer 13. In the phase 2 studies of droloxifene, the prevalence of all prolapse disorders in over 1000 women was 10%, the same in both the treatment and control arms 14.…”
Section: Serm Effects In Reproductive Tissuesmentioning
confidence: 99%
“…Droloxifene, a structural analogue of tamoxifen (3‐hydroxytamoxifen), behaves as an estrogen agonist in terms of its relation to bone as well as its impact on certain components of the lipid and coagulation profiles 12. Its potential for use in advanced breast cancer was suggested by its ability to modulate plasma sex hormone levels in a direction resembling that seen during tamoxifen treatment in postmenopausal women with breast cancer 13. In the phase 2 studies of droloxifene, the prevalence of all prolapse disorders in over 1000 women was 10%, the same in both the treatment and control arms 14.…”
Section: Serm Effects In Reproductive Tissuesmentioning
confidence: 99%
“…13,14 Preliminary data suggest that it may be useful in advanced breast cancer. 15 The cardiovascular effects of droloxifene in women are unknown. The purpose of the present study was to compare the effects of droloxifene with the effects of conventional estrogen replacement on measures of plasma lipids, coagulation and fibrinolytic factors, and brachial artery flowmediated vasodilation in healthy postmenopausal women.…”
mentioning
confidence: 99%
“…The dose of droloxifene used in that study was 40 mg [41]. Other studies, however, had found droloxifene to express dose-dependent effects on plasma levels of the liver proteins IGF-I, IGFBP-I and SHBG [42][43][44]. In these studies, droloxifene 100 mg daily was found to have an effect on the IGF-system resembling that of tamoxifen 20 or 30 mg daily, while droloxifene 40 mg daily caused smaller changes.…”
Section: Atac-trialmentioning
confidence: 80%